Deficits in the Sensitivity to Pitch Sweeps by School-Aged Children Wearing Cochlear Implants - Deroche, Mickael L. D.; Kulkarni, Aditya M.; Christensen, Julie A.; Limb, Charles J.; Chatterjee, Monita (Frontiers in Neuroscience, 2016)
Sensitivity to static changes in pitch has been shown to be poorer in school-aged children wearing cochlear implants (CIs) than children with normal hearing (NH), but it is unclear whether this is also the case for dynamic changes in pitch. Yet, dynamically changing pitch has considerable ecological relevance in terms of natural speech, particularly aspects such as intonation, emotion, or lexical tone information. Twenty one children with NH and twenty-three children wearing a CI participated in this study, along with eighteen NH adults and six CI adults for comparison. Listeners with CIs used their clinically assigned settings with envelope-based coding strategies. Percent correct was measured in one- or three-interval two-alternative forced choice tasks, for the direction or discrimination of harmonic complexes based on a linearly rising or falling fundamental frequency. Sweep rates were adjusted per subject, in a logarithmic scale, so as to cover the full extent of the psychometric function. Data for up- and down-sweeps were fitted separately, using a maximum-likelihood technique. Fits were similar for up- and down-sweeps in the discrimination task, but diverged in the direction task because psychometric functions for down-sweeps were very shallow. Hits and false alarms were then converted into d’ and beta values, from which a threshold was extracted at a d’ of 0.77. Thresholds were very consistent between the two tasks and considerably higher (worse) for CI listeners than for their NH peers. Thresholds were also higher for children than adults. Factors such as age at implantation, age at profound hearing loss, and duration of CI experience did not play any major role in this sensitivity. Thresholds of dynamic pitch sensitivity (in either task) also correlated with thresholds for static pitch sensitivity and with performance in tasks related to speech prosody.